Exploração da luminescência de filmes finos de ZnO dopados com érbio e európio - Santos, Camila Ianhez Pereira dos (Universidade Federal de São Carlos, 2024)
Trivalent rare earth ions (RE³⁺) possess unique electronic configurations and numerous energy levels, resulting in fascinating optical properties across the visible region. These characteristics open various application perspectives in optoelectronic devices, besides encouraging the development of luminescent materials with REs. In this work, pure and doped (2%) zinc oxide (ZnO) thin films with the REs erbium (Er³⁺) or europium (Eu³⁺) were deposited by Spray Pyrolysis. The films were synthesized under two different conditions, resulting in materials with lower crystallinity (SP group) and higher crystallinity (SO group). The luminescence of the REs was also investigated by varying temperature conditions (25 K - 265 K) and hydrostatic pressure (up to 13.5 GPa). X-Ray Diffraction (XRD) indicated that all materials presented the hexagonal wurtzite phase of ZnO. The pure and doped ZnO films from the SO group exhibited crystallites up to 4x larger than those of the SP group, which also showed a more opaque and rougher surface. UV-Vis spectroscopy measurements showed a shift of ~ 4% in the optical gap energy to lower values in the SP group films. Photoluminescence (PL) spectroscopy revealed an increase of over 200x in the intensity of Eu³⁺ optical emissions when doped in a less crystalline structure. The presence of Stark emission peaks in the Er³⁺-doped ZnO film from the SP group highlighted the significant influence of the crystal field. PL measurements with increasing temperature showed a corresponding increase in Eu³⁺ luminescence intensity, likely due to energy transfer between this ion and ZnO energy levels, caused by intrinsic defects. Additionally, the PL investigation under pressure revealed a decrease in the intensity of all Eu³⁺ optical emissions at 10 GPa. This reduction can be attributed to the consolidation of a phase mixture with hexagonal and cubic structures in the material, as observed in the XRD measurements at the same pressure.
Exploration of the luminescence of ZnO thin films doped with erbium and europium
Keywords: ZnO; Luminescência; Terras-raras; Spray-Pirólise; Pressão; Luminescence; Rare-earths; Spray-Pyrolysis; Pressure; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA